A Study on the Opportunities and Challenges of Agripreneurship with reference to Horticulture in Karnataka State (International Journal of Food and Nutritional Sciences, 2023)
Entrepreneurship has been described as the competence and willingness to develop, organize and manage a business venture along with any of its risks in order to make a profit. While major proportion of start-up businesses have to close due to various internal and external environmental factors. In the era of development of small business enterprises, the Agriprenuership has been emerged as one of the important small business sectors that can contribute significantly to the economy through generation of employment opportunities to the rural youths and nation’s prosperity. In this context horticulture is one of the major area of agribusiness which comprises Cultivation of Medicinal Plants, Floriculture, Nursery, Land Scaping, Horticulture Clinic, Tissue Culture, Vegetables Production and Marketing. The study is an effort carried out to analyse the opportunities and challenges of agripreneurship based on social factors like gender and age in agribusiness associated with horticulture.